Childhood traumatic brain injury; education and medical disability. Issue 3 (19th August 2014) - Nilsson, Johanna; Emanuelson, Ingrid Marie; McNicholl, Declan; Wicks, Beth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Purpose: The purpose of this study is to describe level of education and return to school and employment among children and young adults who sustained a TBI 15 years ago and to analyse the occurrence of any medical disability. Design/methodology/approach Method: The study is descriptive. We used a questionnaire with questions covering education, employment, sick leave, insurance compensation and medical follow-up. Findings Findings: 37 individuals, 17 (45.9 %) women and 20 (54.1 %) men, participated. Just over half (20 individuals, 54.1 %) were in employment, 5 (13.5 %) were unemployed and 4 (10.8 %) received disability pension. Eighteen (48.6 %) individuals had received full compensation from their insurance companies, while 12 (35.3 %) had had their medical disability classified. Twelve (33.3 %) individuals were taking medication and 5 (13.9 %) had been followed by the health care system. The results indicate that people sustaining a TBI are less successful on the labour market than the general population, that relatively few had had their disability classified and that almost 50 % receive no insurance compensation. Originality/value Originality: There are few long-term follow-up studies on brain injuries acquired during childhood, and this study would add to the previous knowledge, as aspects of medical disability and legal compensation are included.